STRATEGI PENGEMBANGAN POTENSI ANAK USIA DINI MELALUI MULTIPLE INTELLIGENCES - Acep (EDUKIDS : Jurnal Inovasi Pendidikan Anak Usia Dini, 2026)
ABSTRACT The development of early childhood potential is an important issue in education because each child possesses unique characteristics and diverse forms of intelligence, while learning practices often remain focused on specific academic aspects, limiting the accommodation of children's varied potentials. This study aims to analyze strategies for developing early childhood potential through the Multiple Intelligences approach. The research employed a library research method with a qualitative descriptive approach. Data were collected from books, journal articles, and previous studies related to the theory of Multiple Intelligences and its implementation in early childhood education, and were analyzed through data reduction, data presentation, and conclusion drawing. The findings indicate that the Multiple Intelligences approach assists educators in identifying and accommodating children's diverse intelligences through more flexible and child-centered learning practices. A synthesis of the literature suggests that this approach can support cognitive, social, emotional, creative, and motor development, while also showing potential to enhance children's learning engagement and self-confidence. In conclusion, the Multiple Intelligences approach can serve as a relevant strategy for supporting the optimization of early childhood potential through inclusive learning that respects individual uniqueness, supported by teachers and a conducive learning environment. ABSTRAK Pengembangan potensi anak usia dini menjadi isu penting karena setiap anak memiliki karakteristik dan kecerdasan yang berbeda, sementara praktik pembelajaran masih sering berfokus pada aspek tertentu sehingga keberagaman potensi anak belum terakomodasi secara optimal. Penelitian ini bertujuan menganalisis strategi pengembangan potensi anak usia dini melalui pendekatan Multiple Intelligences. Penelitian menggunakan metode studi kepustakaan (library research) dengan pendekatan deskriptif kualitatif. Data diperoleh dari buku, artikel jurnal, dan hasil penelitian terkait teori Multiple Intelligences serta implementasinya dalam pendidikan anak usia dini, kemudian dianalisis melalui reduksi data, penyajian data, dan penarikan kesimpulan. Hasil kajian menunjukkan bahwa pendekatan Multiple Intelligences membantu pendidik mengenali dan mengakomodasi keragaman kecerdasan anak melalui pembelajaran yang lebih fleksibel dan berpusat pada peserta didik. Sintesis literatur mengindikasikan bahwa pendekatan ini dapat mendukung perkembangan kognitif, sosial, emosional, kreativitas, dan keterampilan motorik, sekaligus menunjukkan potensi dalam meningkatkan keterlibatan belajar serta kepercayaan diri anak. Kesimpulannya, pendekatan Multiple Intelligences dapat menjadi strategi yang relevan untuk mendukung optimalisasi potensi anak usia dini melalui pembelajaran yang inklusif dan sesuai dengan keunikan individu, dengan dukungan guru dan lingkungan belajar yang kondusif.